The Community and UK Wastewater Policies: A Case Study of a Pipe Manufacturing Company (Water Nepal, 2004)
This paper discusses some of the emerging and existing pressures the European Union has placed on wastewater discharges. It reviews two main directives, the Water Framework Directive and the Urban Wastewater Treatment Directive of the European Community. Furthermore, it discusses UK water policies and process of transforming directives into national laws. This paper highlights concepts such as best available techniques, best practical environmental options, certified Environmental Management Systems (EMS) and the role of regulators with reference to a case study of preventing water pollution. Finally, it explains the mechanisms by which UK companies are encouraged to adopt a sustainable approach to wastewater management.Water Nepal Vol.11, No.1, 2004, pp.17-28